Active site-directed inhibition of Ca2+/calmodulin-dependent protein kinase type II by a bifunctional calmodulin-binding peptide. - Kelly, P T (1988)
The activation of Ca2+/calmodulin (CaM)-dependent protein kinase II (CaM-KII) by Ca2+/CaM results in autophosphorylation and the generation of Ca2+/CaM-independent enzyme activity. We postulated that CaM binding and subsequent autophosphorylation alters the conformation of CaM-KII and exposes its substrate-binding and catalytic site(s). Previous peptide mapping studies on CaM-KII demonstrated the close proximity of CaM-binding and autophosphorylation domains. Analyses of the deduced amino acid sequences encoding CaM-KII have allowed the identification of its CaM-binding domain and have revealed two consensus phosphorylation sites that flank this regulatory domain. We report herein the distinct properties of two synthetic peptides modeled after the CaM-binding domain of CaM-KII. The first peptide binds CaM in a Ca2+-dependent manner and is an antagonist of CaM-KII activation (IC50 approximately equal to 75 nM). It does not, however, inhibit CaM-KII activity. A second peptide containing the same CaM-binding domain plus a putative autophosphorylation sequence at its N terminus displayed bifunctional regulatory properties. In addition to being a CaM antagonist, the latter was a potent inhibitor of Ca2+/CaM-independent kinase activity (IC50 approximately equal to 2 microM). We suggest that this bifunctional peptide represents an active site-directed inhibitory element of CaM-KII. The separation of CaM antagonist and active site-directed inhibitory properties of this peptide distinguishes CaM-KII from other CaM-dependent enzymes in which bifunctional regulatory properties appear to reside in the same peptide domain. These results indicate that the definition of site-directed inhibitory peptides should, in some cases, be expanded to include bona fide phosphorylation sites.